Mitochondrial Rab GAPs govern autophagosome biogenesis during mitophagy - Koji Yamano; Adam I Fogel; Chunxin Wang; Alexander M van der Bliek; Richard J Youle (eLife, 2014)
Damaged mitochondria can be selectively eliminated by mitophagy. Although two gene products mutated in Parkinson’s disease, PINK1, and Parkin have been found to play a central role in triggering mitophagy in mammals, how the pre-autophagosomal isolation membrane selectively and accurately engulfs damaged mitochondria remains unclear. In this study, we demonstrate that TBC1D15, a mitochondrial Rab GTPase-activating protein (Rab-GAP), governs autophagosome biogenesis and morphology downstream of Parkin activation. To constrain autophagosome morphogenesis to that of the cargo, TBC1D15 inhibits Rab7 activity and associates with both the mitochondria through binding Fis1 and the isolation membrane through the interactions with LC3/GABARAP family members. Another TBC family member TBC1D17, also participates in mitophagy and forms homodimers and heterodimers with TBC1D15. These results demonstrate that TBC1D15 and TBC1D17 mediate proper autophagic encapsulation of mitochondria by regulating Rab7 activity at the interface between mitochondria and isolation membranes.